2020
DOI: 10.1002/anie.202006280
|View full text |Cite
|
Sign up to set email alerts
|

TEAD–YAP Interaction Inhibitors and MDM2 Binders from DNA‐Encoded Indole‐Focused Ugi Peptidomimetics

Abstract: DNA-encoded combinatorial synthesis provides efficient and dense coverage of chemical space around privileged molecular structures. The indole side chain of tryptophan plays a prominent role in key, or "hot spot", regions of protein-protein interactions. A DNA-encoded combinatorial peptoid library was designed based on the Ugi four-component reaction by employing tryptophan-mimetic indole side chains to probe the surface of target proteins. Several peptoids were synthesized on a chemically stable hexathymidine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 39 publications
0
41
0
5
Order By: Relevance
“…A DNA-encoded, indole-focused combinatorial library of 8112 compounds was screened against TEAD with the goal of identifying PPIDs that disrupt the YAP-TEAD interaction [ 37 ]. The indole-focused library is expected to exploit the crucial PPI interactions mediated by the indole ring of the tryptophan residues in proteins.…”
Section: Compounds That Occupy the Central Pocketmentioning
confidence: 99%
See 1 more Smart Citation
“…A DNA-encoded, indole-focused combinatorial library of 8112 compounds was screened against TEAD with the goal of identifying PPIDs that disrupt the YAP-TEAD interaction [ 37 ]. The indole-focused library is expected to exploit the crucial PPI interactions mediated by the indole ring of the tryptophan residues in proteins.…”
Section: Compounds That Occupy the Central Pocketmentioning
confidence: 99%
“…As only the transactivation domain of TEAD was used in this assay, it will be interesting to deduce whether the compound induces a conformational change in TEAD upon binding. Unfortunately, in HEK 293 cells, compound 9 did not inhibit the expression of CTGF, a YAP-TEAD target gene [ 37 ]. Intriguingly, the efficacy is better when compound 9 is combined with a hippo kinase inhibitor.…”
Section: Compounds That Occupy the Central Pocketmentioning
confidence: 99%
“…A recent study identified molecules disrupting TEAD-YAP interactions by screening a DNA-encoded library. Two inhibitors against the protein-protein interaction exhibited IC 50 s of 6.75 µM and 5.65 µM, respectively [82]. TEADs contain a conserved hydrophobic pocket in its YAP-binding domain (YBD).…”
Section: New Druggable Sites and Novel Function Derived From Structuresmentioning
confidence: 99%
“…hTEAD4/YAP : Dysregulation of protein–protein interactions between transcriptional enhancer factor‐1 domains (TEAD1‐4) and co‐transcription factor Yes‐associated protein (YAP), late Hippo signaling pathway effectors, is associated with oncogenic mechanisms [105–107] . Recently, screening of a small thymidine‐initiated DEL (tiDEL) of peptidomimetics against YAP‐interacting domain of human TEAD4 (hTEAD4) led to the identification of two PPI inhibitors 11 (Figure 5, IC 50 =6.75 μM) and 12 (IC 50 =5.65 μM) [108] . This library was synthesized around the tryptophan side chain as an “anchor motif” with indoles introduced into the library via Ugi four‐component reaction as tryptophan mimetics and CuAAC for library diversification.…”
Section: Inhibition Of Protein–protein Interactionsmentioning
confidence: 99%
“…Both compounds showed hTEAD4/YAP interaction inhibition, however, only compound 11 exhibited inhibition of the palmitic acid‐hTEAD4 interaction that takes place in the so called “central pocket” of hTEAD. Notably, compound 11 demonstrated perturbation of the expression of CTGF gene which is under control of these Hippo pathway effectors [108] …”
Section: Inhibition Of Protein–protein Interactionsmentioning
confidence: 99%